SPONTANEOUS PNEUMOPERITONEUM IN A SEVEN DAY OLD INFANT - Luhulima, Franky; Kardana, Made; Artana, IW Dharma; Junara, Putu; Dharmajaya, IM (Medicina, 2012)
The term pneumoperitoneum is used to describe the presence of free gas or air within the peritoneal cavity. Spontaneous pneumoperitoneum or “non-surgical” pneumoperitoneum is a pneumoperitoneum. not associated with a perforated viscus. This pneumoperitoneum is rare at any pediatric age. In the pediatric population, nonsurgical pneumoperitoneum occurs in 1% to 3% of mechanically ventilated infants, depend on the mode of the ventilation. Pneumoperitoneum without gastrointestinal perforation on the other hand is very rare, and this is usually seen in neonates with respiratory distress and on mechanically ventilator or CPAP. We reported a case of spontaneous pneumoperitoneum in a seven day old infant . The infant presented with a sudden abdominal distention and dyspnea. Plain abdominal x-ray showed a radiolucency image in the superior abdomen. In this patient is done the act of a needle aspirations for drainage air in the peritonium. This patient recovered well a[er done such action by pediatric surgical